Evaluation of Anxiety Levels of Bintang Prima SGO Karate Dojo Athletes - Fajrial, Jul; Putra, Sukardi; Wahdi, Arif; Karimuddin, Karimuddin; Isdarianti, Novi Lidya (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objectives. This study aimed to determine the anxiety levels of Dojo Bintang Prima SGO karate athletes during competitions using a descriptive quantitative approach. Anxiety negatively impacts an athlete's performance and was found to be high among the observed athletes. Materials and methods. The study involved 15 athletes from the Bintang Prima SGO Karate Dojo. In this study, the entire population was considered as the sample or the total side. The data was collected using a closed questionnaire known as SCAT (Sport Competition Anxiety Test). The questionnaire comprised 15 Likert scale questions, where participants had to choose their answers based on their feelings or experiences before competing. The answer choices were